Analisis Pengaruh Kebijakan Moneter terhadap Pertumbuhan Ekonomi - Jusniwati Zai; Reydel Baginsa Lahagu; Mardiana Halawa; Romana Rinda Nazara (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the effect of monetary policy on economic growth in Indonesia. Monetary policy is an important instrument in maintaining macroeconomic stability and supporting growth, through regulating interest rates, money supply, minimum reserve requirements, and open market operations. This study uses a qualitative descriptive approach by analyzing the role of each monetary indicator and its impact on the real sector. The results of the study indicate that effectively implemented monetary policy is able to stabilize inflation, regulate banking liquidity, maintain the stability of the rupiah exchange rate, and support sustainable economic growth. In addition, the implementation of a dual monetary system in Indonesia provides additional flexibility in monetary management. This study also emphasizes the importance of harmonious coordination between monetary and fiscal policies in order to create optimal synergy in achieving national economic goals.